What are the Key Drivers of Future Supply Chains? - Penina Orenstein; Daniel Ladik; Sean Rainford (Journal of Accounting, Business and Management (JABM), 2016)
While there are many factors that can influence the direction of supply chains, we believe that there are a distinct set of emerging trends that stand to define the field and the study over the next several years. These are (a) big data giving way to fast data, (b) the advent of the social supply chain era, and (c) the rise of the knowledge workers. This paper discusses how these three broad areas are transforming the future of supply chain management both from an individual perspective, as well as, using an interrelated approach